Individual support planning: perceptions and expectations of people with intellectual disabilities in the Netherlands. (14th September 2012) - Herps, M. A.; Buntinx, W. H. E.; Curfs, L. M. G.
Abstract: Background  According to Dutch jurisdiction, individual support plans (ISP) should register the mutual agreements between a person with intellectual disabilities (ID) and a professional service organisation with respect to the support that will be provided. In planning for support, active involvement of both parties is necessary. The current study focuses on the perceptions and experiences of Dutch persons with ID with respect to their involvement in their ISP. Method  Data were gathered through semi‐structured interviews with 61 people with mild to moderate ID. Participants were recruited in 23 Dutch service provider organisations. A systematic qualitative analysis was performed on the interview transcripts. Results  Although persons with ID are present at their ISP meeting, active client involvement in developing, executing and evaluating the ISP is not common practice. Issues of accessibility and lack of control over the process and content of ISP hamper effective involvement of people with ID. Conclusions  The study raises questions concerning ISP practices in the Netherlands. The question needs to be addressed as to how to facilitate active involvement of people with ID in planning for support. The results further suggest that support organisations perceive an ISP rather as a formal document to comply with bureaucratic rules than as an instrument of empowerment to enhance control of persons with ID over their own lives.